Treatment adherence and its efficacy in real circumstances in patients with first grade arterial hypertension - T. A. Mangileva (Кардиоваскулярная терапия и профилактика)
Aim. In patients with arterial hypertension (AH) of 1 grade to find out the effectiveness of blood pressure (BP) control during long-termobservation in real life conditions and to check the factors that mighthelp with a decision either to prescribe medical treatment or keep on life style modification.Material and methods. Two times, with the interval 71,3±1,5 months,66 patients with AH 1 grade were assessed, among those were moderate, moderate-high, high and very high additional cardiovascular risks.Together with other investigations, all patients at baseline and repeatedly underwent office BP measurement, ambulatory monitoring (ABPM) and body mass check. At primary assessment, the detailed recommendationswere given on the normalization of life style and pharmacotherapy.During second assessment, the adherence of patients to medical andlife style treatment was evaluated.Results. With the time, most patients with AH 1 grade had a decrease of BP level, most prominent in patients with higher risk. Only in the highest risk group, there was no BP dynamics. Among all studied, as separately in groups with moderate, moderate-high, high and very high levels, during follow-up there were no differences in BP levels between patients adhering medical therapy and others. The worst adherence was found in moderate risk patients. The best results of body mass index decrease and increase of aerobic physical exercises showed the patients with relatively high glucose level and endothelial vascular factor in blood.Conclusion. During long-term observation in real circumstances, mostpatients with 1 level AH, knowing about medical and non-medical BPcontrol tools, show its decrease. The level of additional cardiovascularrisk, glucose level and vascular endothelial factor in blood might serve as adherence predictors and treatment effectiveness estimate.